2008
DOI: 10.1016/j.virol.2007.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Specific in vivo expression in type II pneumocytes of the jaagsiekte sheep retrovirus long terminal repeat in transgenic mice

Abstract: Jaagsiekte sheep retrovirus (JSRV) is the causative agent of ovine pulmonary adenocarcinoma, a transmissible lung cancer in sheep. Previous experiments in differentiated murine tissue culture cell lines suggested that the disease specificity of JSRV for secretory lung epithelial cells (type II pneumocytes an Clara cells) reflects transcriptional specificity of the viral long terminal repeat (LTR) for these cells. To test this in vivo, transgenic mice carrying the bacterial beta-galactosidase (beta-Gal) gene dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…The JSRV LTRs contains lung-specific enhancer binding motifs that are preferentially active in cell lines derived from transformed type 2 pneumocytes [80] [83] . In addition, in transgenic mice, reporter gene expression driven by the JSRV LTR has been detected specifically in type 2 pneumocytes [84] . Thus, JSRV-host equilibrium has been reached by a combination of factors.…”
Section: Discussionmentioning
confidence: 99%
“…The JSRV LTRs contains lung-specific enhancer binding motifs that are preferentially active in cell lines derived from transformed type 2 pneumocytes [80] [83] . In addition, in transgenic mice, reporter gene expression driven by the JSRV LTR has been detected specifically in type 2 pneumocytes [84] . Thus, JSRV-host equilibrium has been reached by a combination of factors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in transgenic mice carrying a beta-galactosidase reporter gene under the control of the JSRV LTR, reporter activity was predominantly restricted to type II pneumocytes (16). In a separate study, infection of mice with adeno-associated virus vectors expressing JSRV Env resulted in tumors with a bronchioloalveolar distribution similar to those seen in sheep (87).…”
mentioning
confidence: 95%
“…In previous studies, the JSRV LTR was found to be preferentially active in MLE-15 and mtCC1-2 mouse cell lines derived from alveolar type II pneumocytes (ATII) and Clara cells, respectively (22,23,27), while in transgenic mice carrying a bacterial ␤-galactosidase gene driven by the JSRV LTR, expression was limited to ATII cells and not detected in Clara cells or in any other tissues (8). However, none of these studies examined the function of the JSRV LTR in the nasal epithelium.…”
Section: Discussionmentioning
confidence: 94%